2011
DOI: 10.2478/v10298-012-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought stress and polymer on osmotic adjustment and photosynthetic pigments of sunflower

Abstract: Water stress affects plant growth and crop productivity in the vast semi-arid and arid regions of Iran. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…These results suggested that proline accumulation in faba bean leaves under well water and increased with increasing the drought stress in faba bean genotypes not related to faba bean types however major type was higher in all treatments. In other field crops it was found that proline content was higher after droughtin wheat (Vendruscolo et al, 2007 andJohari-Pireivatlou, 2009), Pea (Alexieva et al, 2001), Chickpea (Mafakheri et al, 2010), Sugar Beet (Putnik-Delic et al, 2013), Sesame (Kadkhodaie et al, 2015), Sunflower (Nazarli et al, 2011), upland Rice (Lumet al, 2014 and Cotton (Zhang et al, 2014). Over all water treatments proline content was in highly significant negative relationship with seed yield (r= -0.65**, P<0.01) indicated that exposing faba bean plants to drought accumulation of proline in leaves increased and seed yield decreased.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that proline accumulation in faba bean leaves under well water and increased with increasing the drought stress in faba bean genotypes not related to faba bean types however major type was higher in all treatments. In other field crops it was found that proline content was higher after droughtin wheat (Vendruscolo et al, 2007 andJohari-Pireivatlou, 2009), Pea (Alexieva et al, 2001), Chickpea (Mafakheri et al, 2010), Sugar Beet (Putnik-Delic et al, 2013), Sesame (Kadkhodaie et al, 2015), Sunflower (Nazarli et al, 2011), upland Rice (Lumet al, 2014 and Cotton (Zhang et al, 2014). Over all water treatments proline content was in highly significant negative relationship with seed yield (r= -0.65**, P<0.01) indicated that exposing faba bean plants to drought accumulation of proline in leaves increased and seed yield decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the level of proline accumulated in natural polymer-treated plants under water stress was not as high as in water-stressed plants without natural polymers. Similarly, by applying of natural polymers, the reduced proline accumulation was found in sunflower (Nazarli et al, 2011) and in Tomato (Ullah et al, 2016).…”
Section: Fc 100% Fc 75% Fc 50%mentioning
confidence: 90%
“…Robiul Islam et al [22] reported that 15 kg ha −1 of SAP plus 150 kg ha −1 of nitrogen was the optimum rate for sustainable corn production, which maintains proper nutrient balance in the soil, increased plant height, stem diameter, leaf area, biomass accumulation and relative water content, as well as the protein and sugar contents in the grain. It is widely accepted that SAP could be an advantage for plants against drought stress [21] mainly through improved water-use efficiency [15].…”
Section: Introductionmentioning
confidence: 99%